Lesion Distribution and Early Changes of Right Hemisphere in Chinese Patients With Post-stroke Aphasia - Fan, Ruiwen; Gao, Ying; Zhang, Hua; Xin, Xiyan; Sang, Feng; Tan, Zhongjian; Zhang, Binlong; Li, Xiaolin; Huang, Xing; Li, Shuren; Chang, Jingling (Frontiers in Aging Neuroscience, 2021)
The role of the right hemisphere (RH) in post-stroke aphasia (PSA) has not been completely understood. In general, the language alterations in PSA are normally evaluated from the perspective of the language processing models developed from western languages such as English. However, the successful application of the models for assessing Chinese language functions in PSA patients has not been reported. In this study, the features of specific language-related lesion distribution and early variations of structure in RH in Chinese PSA patients were investigated. Forty-two aphasic patients (female: 13, male: 29, mean age: 58±12 years) with left hemisphere injury between one and six months after stroke were included. The morphological characteristics, both at the levels of grey and white matter, were quantified by 3T multiparametric brain MRI-imaging. Fridriksson et al.´s (2016) dual-stream model were used to compare with language-related lesion regions. Voxel-based lesion-symptom mapping (VLSM) analysis has been undertaken. Our results showed that lesions in precentral, superior frontal, middle frontal, postcentral gyri were responsible for both production and comprehension dysfunction of Chinese PSA patients and were quite different from the lesions described by the Fridriksson et al. ´s dual-stream model. Furthermore, gray matter volume (GMV) was found significantly decreased in RH, and white matter integrity was disturbed in RH after LH injury in Chinese PSA patients. The different lesion patterns between Chinese PSA patients and English-speaking PSA patients may indicate that Fridriksson et al´s dual-stream model is not suitable for the assessment of Chinese language functions in Chinese PSA patients in subacute phase of recovery. Moreover, decreased structure integrity in RH was found in Chinese PSA patients.